Nahdlatul Ulama Dalam Pusaran Politik: Sebuah Otokriktik Orientasi NU Dalam Politik Perspektif Insider - Mahathir Muhammad Iqbal (Universitas Islam Malang, 2019)
A healthy and strong democratic state does not only require a strong political world. Of course, it is important to have a strong party, a strong leader, and a strong government. However, democracy also requires civil society which is also healthy and strong. In the political science literature, the political world and civil society are distinguished by political positions. The world of politics is the political territory of citizens who are prepared to fight for positions of government. The main vehicle is a political party. Meanwhile, civil society is the area of activity for citizens outside the government. The main vehicle is mass organizations. Deliberately, the world of civil society did not want to take part in the power struggle for the position of government. They deliberately chose a position outside the government to control the government. NU is expected to be in this position. Who always kept his distance from the world of practical politics and power. That way, the independence of NU as an authoritative mass organization is maintained.